PENCEGAHAN STUNTING DI POSYANDU RW 010 KELURAHAN KROBOKAN KOTA SEMARANG - Anifatus Sa'adah; Fenny Wiji Astuti; Mutiara Dewi Masithah; Ovikariani; Diamonda Adinda Kirana; Syahkrirotul Exma; Dea Ayu Amalia; Mela Ananda Putriana (Jurnal Pengabdian IKIFA, 2024)
Stunting is a significant problem that requires attention as it is linked to cognitive and motor skills, as well as overall performance. One approach to preventing stunting is to enhance public knowledge through education for pregnant women and mothers with toddlers. The method used for distributing leaflets involves explaining the content and engaging in question and answers sessions with the participants. The target audience for this counseling session is pregnant women and mothers with children under five. The event took place on Saturday, June 10, 2023, at RW 010, Krobokan, West Semarang. The counseling session was successful in reaching its objectives and was well-received. Participants were able to grasp the material and enhance their understanding of stunting.